2001
DOI: 10.1086/322023
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Serum IgG Antibodies Specific forWolbachiaSurface Protein in Rhesus Monkeys Infected withBrugia malayi

Abstract: The mechanism of lymphedema development in individuals with lymphatic filariasis is presently poorly understood. To investigate whether Wolbachia, symbiotic bacteria living within filarial nematodes, may be involved in disease progression, Wolbachia-specific immune responses were assayed in a group of Brugia malayi-infected rhesus monkeys. Serum IgG antibodies specific for a major Wolbachia surface protein (WSP) were detected in 2 of 12 infected monkeys. It is interesting that both of these monkeys developed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
2
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 15 publications
1
43
2
2
Order By: Relevance
“…Bazzocchi et al (5) reported the universal production of anti-WSP antibodies in Dirofilaria immitis-infected cats, suggesting that the constant release of Wolbachia organisms through natural worm death was sufficient to induce an antibody response. In contrast, others have reported an increase in antibodies to WSP in two B. malayi-infected rhesus monkeys only at the time of transition from microfilaremic to amicrofilaremic status and during attacks of lymphedema (41).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Bazzocchi et al (5) reported the universal production of anti-WSP antibodies in Dirofilaria immitis-infected cats, suggesting that the constant release of Wolbachia organisms through natural worm death was sufficient to induce an antibody response. In contrast, others have reported an increase in antibodies to WSP in two B. malayi-infected rhesus monkeys only at the time of transition from microfilaremic to amicrofilaremic status and during attacks of lymphedema (41).…”
Section: Discussionmentioning
confidence: 69%
“…Gerbils were bled throughout the course of infection and at necropsy. Blood was examined for microfilariae, and sera were harvested for the analysis of antibodies against Wolbachia surface protein (WSP) (41). Necropsies and worm recoveries were performed at 76, 86, and 100 DPI.…”
Section: Gerbils and Parasitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Wolbachia is not the target of the antibody response in immunized wild-type or TLR4-mutant mice, suggesting that the immune response does not target Wolbachia in order to mediate larval killing. Even though the antibody response against Wolbachia proteins may be an effective way to determine disease outcome for lymphatic filariasis (28,29), it appears to be a poor indicator of protective immunity against larval O. volvulus in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the inflammation induced by filarial infection are poorly understood, but studies of humans with natural infection and experimental animals exposed to live filaria or soluble extracts of the organisms have implicated a role for both adaptive and innate immunity (1)(2)(3). The remarkable observation that W. bancrofti, B. malayi, and O. volvulus harbor endosymbiotic Wolbachia bacteria (4 -6) has raised the possibility that infected individuals respond to these organisms in addition to nematode ligands and that Wolbachia can initiate or promote inflammation (7)(8)(9)(10)(11)(12). Despite remarkable longevity in the human host (13), adult filarial worms themselves are not strong inducers of inflammation (3,14).…”
mentioning
confidence: 99%